Early Mobilization Decision after an Acute Ischemic Stroke: Protocol for an Umbrella Review - Fernandes, C (2024)
Introduction: Stroke is considered one of the greatest public health challenges worldwide, with the ischemic subtype being the most prevalent. Various acute stroke clinical guidelines recommend early rehabilitation interventions, including very early mobilization. However, despite the studies conducted in recent years regarding when to initiate mobilization after an acute stroke, there are few systematic and personalized protocols based on the factors for which patient mobilization should ideally be performed. We aim to conduct an umbrella review of systematic reviews and meta-analyses to study the early mobilization decision after an acute ischemic stroke in comparison with conventional care and correlate the different approaches with patient clinical outcomes. Methods and analysis: We will perform a systematic search on PubMed/MEDLINE, EMBASE, Cochrane Database of Systematic Reviews, Epistemonikos and Web of Science Core Collection databases. Retrieved studies will be independently reviewed by two authors and any discrepancies will be resolved by consensus or with a third reviewer. Reviewers will extract the data and assess the risk of bias in the selected studies. We will use the 16-item Assessment of Multiple Systematic Reviews 2 (AMSTAR2) checklist as the critical appraisal tool to assess cumulative evidence and risk of bias of the different studies. This will be the first umbrella review that compares early mobilization approaches in post-acute ischemic stroke. This study may help to define the optimal early mobilization strategy in stroke patients. PROSPERO registration number: CRD42023430494.